2017
DOI: 10.1016/j.jcol.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profile, risk factors and therapeutic approach of desmoid tumors in familial adenomatous polyposis

Abstract: Introduction Desmoid tumors are the main extraintestinal manifestation of FAP, presenting high morbidity and mortality. It is a neoplasia without metastasis capacity, but with infiltrative growth and with a high rate of recurrence. In familial forms, these tumors are associated with a germinal mutation in the APC gene, with a genotype–phenotype correlation influenced by other risk factors. Materials and methods A review of articles published since the year 2000 in Portuguese, English or Spanish on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…DT may arise sporadically or in the context of an extra-colic manifestation of FAP, and may be intra-abdominal, located in the abdominal wall, or extra-abdominal 5 , 10 , 11. They comprise only 0.03% of all neoplasms and 3% of all soft tissue tumors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DT may arise sporadically or in the context of an extra-colic manifestation of FAP, and may be intra-abdominal, located in the abdominal wall, or extra-abdominal 5 , 10 , 11. They comprise only 0.03% of all neoplasms and 3% of all soft tissue tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, surgical trauma may be implicated as one of the factors capable of leading to the development of DT, and appears unrelated to a specific type of surgery 8. Nevertheless, some authors observed a lower incidence of DT in laparoscopic versus open procedures, so minimally invasive approaches might presumably reduce the risk of the occurrence of DT after prophylactic colectomy in patients with FAP 10 , 19…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations